The Effect of Botanical Nutrients Enriched with Trichoderma sp. on the Growth of Cocoa Seed Radicles (Theobroma cacao L.) - qomariyah, mahyatul; Mudakir, Imam; Puspita Sari, Niken (Pelita Perkebunan (a Coffee and Cocoa Research Journal), 2025)
Cocoa (Theobroma cacao L) is a plant that is widely cultivated by the Indonesian people. Many cocoa farmers experience crop failure due to pests and diseases. One effort that can be made to reduce this problem is to create high-quality cocoa seeds that are able to survive when attacked by pests and diseases. This study aims to investigate the effect of adding nutrients in the form of biosaka and Trichoderma sp. to cocoa seed soaking water on radicle length. The biosaka treatment used three different formulas: A: control, B: formula 1 (a mixture of weeds and water shoots in a 1:1 ratio), B: formula 2 (a mixture of weeds and water shoots in a 2:1 ratio), and C: formula 3 (a mixture of weeds and water shoots in a 1:2 ratio). Each biosaka solution was mixed with Trichoderma sp. at a dilution of 10-1, and the treatment was repeated three times, with three cocoa seeds in each replicate. The results obtained indicate that the best biosaka formula for cocoa seed radicle length, spore count, and spore density of Trichoderma sp. is the biosaka with a weed and water sprout ratio of 2:1 mixed with Trichoderma sp. at a dilution of 10 L .